Patient-assessed quality of care in type 2 diabetes in a German nationwide health survey 2017. (30th September 2020) - Baumert, J; Schmid, G L; Du, Y; Paprott, R; Carmienke, S; Stühmann, L M; Frese, T; Heidemann, C; Scheidt-Nave, C
Abstract: Background: Patient-assessed quality of chronic illness care is important to guide medical care for patients with diabetes and other complex chronic diseases, but information from epidemiological studies is scarce. Thus, we examined self-assessed quality of care among adults with type 2 diabetes (T2D) based on a population-based design. Methods: The study population was drawn from a nationwide survey on diabetes-related knowledge and information needs conducted in Germany in 2017 and included participants aged ≥18 years with known type 2 diabetes (T2D) in the last 12 months (n = 1, 328). A German short version of the "Patient assessment of chronic illness care (PACIC-DSF)" consisting of 9 items based on 5-point Likert scale was applied to assess self-reported quality of care in diabetes which was operationalized by a standardized PACIC sum score ranging from 1 to 5. Linear regression with different stages of adjustment was applied to assess the association of basic characteristics and diabetes-related factors with the PACIC score. Results: Quality of care was assessed less favorably by women than by men (PACIC score: 2.38 vs. 2.47) overall and decreased along with age. The PACIC score significantly increased in participants with insulin use (β = 0.16, p = 0.024), ever participating in a diabetes education program (β = 0.33, p < 0.001), following a diet plan at least once a week (β = 0.33, p < =0.001) as well as performing daily self-examination of feet (β = 0.14, p = 0.023), self-control of blood glucose (β = 0.34, p < 0.001), and being physically active for at least 30 min (β = 0.21, p < 0.001) compared to participants without the respective trait. Conclusions: Self-assessed quality of care by adults with known T2D from this population-based study is moderate and seems lower compared to findings from clinical studies. Key messages: An active involvement of people with type 2 diabetes into the implementation of care is essential and may contribute to improved self-perceived quality of care. To identify and overcome obstacles in diabetes care based on the patient's perspective remains a public health challenge.